2020
DOI: 10.1038/s41586-020-2565-5
|View full text |Cite|
|
Sign up to set email alerts
|

Coupling dinitrogen and hydrocarbons through aryl migration

Abstract: A persistent challenge in chemistry is to activate abundant, yet inert molecules such as hydrocarbons and atmospheric N 2 . In particular, forming C–N bonds from N 2 typically requires a reactive organic precursor 1 , which limits the ability to design catalytic cycles. Here, we report an diketiminate-supported iron system that is able to sequentially activate benzene and N 2 to form aniline derivatives. The key to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 50 publications
5
120
0
2
Order By: Relevance
“…The potential of alkali‐metal mediation in this arena is emphatically demonstrated in the reduction of dinitrogen and its hydrogenation to ammonia by a well‐defined potassium‐iron complex, as reported by the Holland group [73a] . More recently, the same group showed that a mixed sodium‐iron complex can functionalise dinitrogen through coupling reactions with hydrocarbons [73b] . A review on this related theme is likely to follow in the future.…”
Section: Discussionmentioning
confidence: 82%
“…The potential of alkali‐metal mediation in this arena is emphatically demonstrated in the reduction of dinitrogen and its hydrogenation to ammonia by a well‐defined potassium‐iron complex, as reported by the Holland group [73a] . More recently, the same group showed that a mixed sodium‐iron complex can functionalise dinitrogen through coupling reactions with hydrocarbons [73b] . A review on this related theme is likely to follow in the future.…”
Section: Discussionmentioning
confidence: 82%
“…All the geometries were fully optimized by the density functional theory (DFT) method with the (U)B3LYP [75] density functional in the toluene solvent as previous report [47,76,77] . The solvent effect was considered with the solution model density (SMD) [78] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the same year, Xi and his co‐workers reported direct synthesis of hydrazine and its derivatives from dinitrogen promoted by scandium complexes [45,46] . Very recently, Holland's group reported an iron‐catalyzed coupling of benzene and nitrogen [47] . In addition, metal‐free dinitrogen activation has also been initiated recently [48,49] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Since the first N 2 complex of at ransition metal was reported in 1965, [6] chemists endeavor to explore molecular systems which can be utilized for fixation and activation of N 2 under mild conditions. [7][8][9][10][11][12][13][14] In the past few decades,aseries of significant advances in the N 2 fixation and activation have been demonstrated by transition metal complexes [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] as well as by organoboron species. [31][32][33][34][35] In addition, molecular uranium systems also exhibit attractive ability for N 2 binding,r eduction, and activation.…”
Section: Introductionmentioning
confidence: 99%